Investigation of A PV-Fuel Cell System For Electric Motors - Bayrak, Zehra Ural; Gencoglu, Muhsin Tunay (Ieee, 2013)
Photovoltaic-fuel cell energy systems have been popular as energy production systems at the present time. These energy sources are clean, environmental-friendly, modular, and independent from fossil fuels. The costs of current solar-hydrogen systems are likely to fall with technological development and larger-volume production of key components such as electrolyser, fuel cells and hydrogen storages. In this study, model of a PV-Fuel Cell System has been developed using Matlab/Simulink, consist of a PV cell, fuel cell, electrolyser, converter, inverter and electric motors. PV panels have been used for supply DC electricity to the electrolyser. The electrolyser has been used to produce hydrogen for storage. Thus, the fuel cell can use this hydrogen for energy production when there is no sunlight. DC and AC electric motors are used for exhibit characteristic of fuel cells in different load situation.
International Conference on Renewable Energy Research and Applications (ICRERA) -- OCT 20-23, 2013 -- Madrid, SPAIN
Keywords: fuel cell; PV cell; electric motors; modelling